2023
DOI: 10.1007/s11356-023-28588-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced removal of perfluorooctanoic acid with sequential photocatalysis and fungal treatment

Abstract: In this paper, we report the degradation of perfluorooctanoic acid (PFOA), which is a persistent contaminant in the environment that can severely impact human health, by exposing it to a photocatalyst, bismuth oxyiodide (BiOI), containing both Bi4O5I2 and Bi5O7I phases and a fungal biocatalyst (Cunninghamella elegans). Individually, the photocatalyst (after 3 h) and biocatalyst (after 48 h) degraded 35–40% of 100 ppm PFOA with 20–30% defluorination. There was a marked improvement in the degree of degradation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A combination of approaches is one potential mechanism to ameliorate the effects of inhibition. For example, by combining sequential photocatalysis and fungal treatment (Khan et al 2023 ) were able to improve the degradation of perfluorooctanoic acid (PFOA). It was suggested that the photocatalysis step reduced the initial concentration of the PFOA without producing the inhibitory 5:3 FTCA, allowing the fungus to remain active for longer, thus leading to an overall improved degradation of the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of approaches is one potential mechanism to ameliorate the effects of inhibition. For example, by combining sequential photocatalysis and fungal treatment (Khan et al 2023 ) were able to improve the degradation of perfluorooctanoic acid (PFOA). It was suggested that the photocatalysis step reduced the initial concentration of the PFOA without producing the inhibitory 5:3 FTCA, allowing the fungus to remain active for longer, thus leading to an overall improved degradation of the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…[ 69 ] This allows spectral absorption in the VIS region and narrows the energy gap of the materials to values below 2 eV while maintaining efficient charge separation [69b] . Indeed, numerous BiOX materials, including BiOCl, [ 70 ] BiOI, [ 71 ] BIOF, [48e] and p–n BiOI–Bi 5 O 7 heterojunctions, have been described for the degradation of PFOA under VIS light irradiation. [ 72 ]…”
Section: Photocatalysts: From Metal Oxides To Engineered Semiconductorsmentioning
confidence: 99%